PENGARUH ELECTRONIC WORD OF MOUTH, BRAND IMAGE DAN BRAND TRUST TERHADAP KEPUTUSAN SISWA MENGIKUTI KURSUS DI KAMPOENG BAHASA ENGLISH COURSE - Oktaviani, Bella; Harwani, Yuli (Journal of Fundamental Management (JFM), 2023)
This research was conducted due to a slight decrease in students attending the course. This study aims to analyze the effect of electronic word of mouth, brand image and brand trust on students' decisions to take courses at Kampoeng Bahasa English Course. The population in this study were 200 students who took English courses at the Kampoeng Language English Course institution for at least 3 months in all grades. The sample used was 133 students, calculated based on the Slovin formula. The sampling method used purposive sampling. Methods of data collection using survey methods, with the research instrument is a questionnaire. The data analysis method in this study is the Structural Equation Model (SEM) with the Smart-PLS version 3.2.9 analysis tool. The results of this study prove that Electronic Word of Mouth, Brand Image and Brand Trust each have a positive and significant effect on students' decisions to take courses at Kampoeng Bahasa English Course.